Interrelación e interdependencia en un territorio tradicional - Narváez-Collaguazo, Roberto Esteban (2024)
The Waorani, people of recent contact, and the family groups in isolation Tagaeiri Taromenane coexist in a particular territory, Yasuní, where the presence of external actors, and the extractive activities, generate conditions of pressure, activating conflicts. The most vulnerable peoples are those who they become victims, as happened in 2003, 2006 and 2013, with massacres that put the peoples in isolation the verge of disappearance. The article is an ethnographic research, for understanding the Waorani culture and of the family groups in isolation, identifying intergroup and intragroup relations, and the elements linked to conflict, which lead to establish the persistence of an ethos warrior and the persistence of a social order in relationships within the traditional territory of these societies.